Embedding CeO2 nanocontainers in a TiO2 coating on glass surfaces - Jacinthe Gagnon; Rachel A. Caruso; Katharina M. Fromm (AIMS Bioengineering, 2017)
Various strategies are being developed for the prevention of implant-related infections. One of them is the encapsulation of antimicrobial drugs in inorganic containers that can be released at the site of the implant. However, the attachment of such containers onto implant surfaces may be a challenge. In this study, it is demonstrated that CeO2 nanocontainers can be added to a TiO2 coating on glass surfaces. The structure, crystal phase and surface properties of the nanocontainers were characterized by transmission electron microscopy, scanning electron microscopy (SEM), powder X-ray diffraction, infrared spectroscopy, Raman spectroscopy and a zetasizer. The coatings were analyzed by SEM and energy-dispersive X-ray spectroscopy to determine their homogeneity and ensure CeO2 encapsulation. The coatings were stable in air over prolonged time periods (> 6 months) and therefore hold promise for pursuing in biomedical applications.